Conditions for the existence of almost periodic solutions of nonlinear differential equations in Banach spaces - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We obtain conditions for the existence of almost periodic solutions of nonlinear almost periodic differential equations in a Banach space without using the H-classes of these equations.